IDENTIFIKASI MUTASI GEN FOLLICLE STIMULATING HORMONE (FSH) PADA ITIK PITALAH SUMATERA BARAT - Stefani Fitri Haryati; K Subekti; F Arlina; Rusfidra Rusfidra; R Amelia (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2023)
The purpose of this study was to identify Follicle Stimulating Hormone (FSH) gene mutation of West Sumatera Pitalah ducks. This study used blood samples from 50 Pitalah ducks (5 males and 45 females). Extraction blood samples was analized by Kit from iNtRON Biotechnology and amplification of DNA extraction used the primer with fragmen target 318 bp. Sequencing was analized by 1st Base Singapore and this product was analized by Dnastar. Based on the result of the study is identify Follicle Stimulating Hormone (FSH) gene mutation of West Sumatera Pitalah ducks. Key Words: FSH, Gene, Mutation, Pitalah Duck, Sequensing